The opposite of unnatural intercourse: understanding Section 377 through Section 375. Issue 3 (2nd September 2017) - Sebastian, John
ABSTRACT: S 377 has again become a hot topic of debate with the Supreme Court recently deciding to set up a bench to hear challenges to its constitutionality. I focus upon one particular argument in the curative petition, which claims that the change in the definition of rape in S 375 of the IPC has an impact on what can be considered criminal under S 377. I shall argue that the law's change in the definition of rape reflects the manner in which societal understandings of sex itself have evolved, because rape is often defined in contrast to the "regulative ideal" of "ordinary" sexual intercourse. Further, this will demonstrate that merely going Naz Foundation 's way of restricting the application of S 377 to non-consensual "unnatural" intercourse is not enough. In order for the new S 375 to make sense, there is no option but for S 377 to be radically reinterpreted.